The psychology of music in multimedia - Tan, Siu-Lan, 1963-; Cohen, Annabel J., 1947-; Lipscomb, Scott David, 1959-; Kendall, Roger A. (Oxford : Oxford University Press, 2013)
For most of the history of film-making, music has played an integral role serving many functions - such as conveying emotion, heightening tension, and influencing interpretation and inferences about events and characters. More recently, with the enormous growth of the gaming industry and the Internet, a new role for music has emerged. However, all of these applications of music depend on complex mental processes which are being identified through research on human participants in multimedia contexts. This is the first book dedicated to this fascinating topic. This book presents a wide range of scientific research on the psychological processes involved in the integration of sound and image when engaging with film, television, video, interactive games, and computer interfaces. Collectively, the rich chapters in this edited volume represent a comprehensive treatment of the existing research on the multimedia experience, with the aim of disseminating the current knowledge base and inspiring future scholarship. The focus on empirical research and the strong psychological framework make this book an exceptional and distinctive contribution to the field. The international collection of contributors represents eight countries and a broad range of disciplines including psychology, musicology, neuroscience, media studies, film, and communications. Each chapter includes a comprehensive review of the topic and, where appropriate, identifies models that can be empirically tested. Part One presents contrasting theoretical approaches from cognitive psychology, philosophy, semiotics, communication, musicology, and neuroscience. Part Two reviews research on the structural aspects of music and multimedia, while Part Three focuses on research examining the influence of music on perceived meaning in the multimedia experience. Part Four explores empirical findings in a variety of real-world applications of music in multimedia.
Introduction : The psychology of music in multimedia / Annabel J. Cohen, Scott D. Lipscomb, Siu-Lan Tan, and Roger A. Kendall -- Models and Multidisciplinary Perspectives. Congruence-Association Model of music and multimedia : origin and evolution / Annabel J. Cohen ; Experimental semiotics applied to visual, sound, and musical structures / Roger A. Kendall and Scott D. Lipscomb ; Integrating media effects research and music psychology / Mark Shevy ; Musical analysis for multimedia : a perspective from music theory / David Bashwiner ; Emotion and music in narrative films : a neuroscientific perspective / Lars Kuchinke, Hermann Kappelhoff, and Stefan Koelsch -- Cross-Modal Relations in Multimedia. Perceived congruence between auditory and visual elements in multimedia / Shin-ichiro Iwamiya ; How pitch and loudness shape musical space and motion / Zohar Eitan ; Cross-modal alignment of accent structures in multimedia / Scott D. Lipscomb -- Interpretation and meaning. Music videos and visual influences on music perception and appreciation : Should you want your MTV? / Marilyn G. Boltz ; Music and memory in film and other multimedia : The Casablanca effect / Berthold Hoeckner and Howard C. Nusbaum -- Applications : music and sound in multimedia. Children's media : The role of music and audio features / Sandra L. Calvert ; Playing with sound : The role of music and sound effects in gaming / Mark Grimshaw, Siu-Lan Tan, and Scott D. Lipscomb ; Music in television advertising and other persuasive media / Mark Shevy and Kineta Hung ; Auditory icons, earcons, and displays : information and expression through sound / Agnieszka Roginska ; Understanding the impact of surround sound in multimedia / Mark Kerins -- Future research directions. Future research directions for music and sound in multimedia / Siu-Lan Tan, Annabel J. Cohen, Scott D. Lipscomb, and Roger A. Kendall.
Includes bibliographical references and indexes.
Keywords: Mass media and music -- Psychological aspects